Contribution toward practical design to improve the planning, implementation, and assessment of the instruction of chemistry teachers - Copriady, Jimmi; Rery, Radjawaly Usman; Zulnaidi, Hutkemri; Alimin, Masnaini (Ekip Buro Makineleri A.S., 2018)
This study aims to identify the contributions of teacher competency on teaching and learning for the subject of chemistry for the practical design, planning, and implementation to assessment of practical exercises in the science laboratory. The study used survey method with a five-point Likert scale questionnaire. The questions focused on designing, planning, implementing, and assessing practical sessions to discover teacher competency in the four listed aspects. Sample consisted of 236 chemistry teachers chosen at random from Riau, Indonesia. Structural Equation Model (SEM) was used to identify the teacher contribution of' practical design, planning, and implementation to assessment of practical exercise. Findings showed that the practical design, planning, implementation of teachers were contributed to assessment of practical exercise. Implementation seemed to be the best predictor contribution to assessment. Based on the findings, a strategic and united effort is necessary to increase the competency of teachers and to develop the latest practical materials.